DIADORIM AS A FEMININE DEVIL IN â€œTHE DEVIL TO PAY IN THE BACKLANDSâ€ - Silva, Carlos (2007)
This analysis deals with the liaison passage – and unsettled – of Riobaldo between Diadorim and Otacília. The myth of Lilith the first incarnation of the feminine devil, is present in the in the love triangle in The Devil to Pay in the Backlands. In this way, the characters enter in other characters to the construction of stories within another story. There is an analogy between the myth Adam and Lilith and Adam and Eve – a conflict of a man between two women, being one agreed with the Devil and another celestial. In the end, Riobaldo gets to salvation and the purification. Key Words: Devil. Myth. Way. Love. Salvation